Reinventing Live: The Always-On Future of Events - Étienne Capron (Communiquer)
How do we imagine the future of events industry since the COVID‑19 crisis? This is the challenge that Denzil Rankine and Marco Giberti tackle in their book Reinventing Live: The Always-On Future of Events (2021). These two professionnals’ call for hybrid event formats is illustrated through a reflective posture and rich case studies.